Thermodynamic and physical-chemical analyses of steam reforming of ethanol: hydrogen production for use in PEMFC - Silveira, José Luz; Silva, Márcio Evaristo; Souza, Antonio Carlos Caetano; Sosa, María Isabel (Revista Ciências Exatas, 2008)
The ethanol is a renewable energy source and has advantages if compared with another fuels. The ethanol production allows the production of “biohydrogen”, that can be used in fuel cells, whose technologies are responsible for lower environmental impact and higher performances of energy generation, among other advantages. The steam reforming uses a catalytic reaction between ethanol and superheated water. In this work, the thermodynamic and physical-chemical analyses of steam reforming of ethanol for hydrogen production, for use in a 1 kW-PEMFC (Proton Exchange Membrane Fuel Cell), allowing the use of hydrogen as energetic vector are preformed. The process steps of steam reforming of ethanol, the operational conditions, the catalysts for acting of the steam reforming reactions, the ratio fuel / steam, considering the process of endothermic reaction of reforming process are described. The volumes of reforming products, considering the production of CO2, H2 and small volumes of non-used reactants in the reforming are also determined. The results are co-related for a higher production of hydrogen.